Tourism destinations and tourist behavior based on community interaction models of film-enabled tourism destinations - Lao, Yongshi; Zhu, Jianfei; Liu, Jinlin (Frontiers in Psychology, 2023)
The importance of media-induced tourism has increased in the latest decade. The integration and collaboration of film elements is an especially effective pathway for the innovative development and upgrading of the experience of the cultural tourism industry. Existing studies on the mechanism of tourism destinations and cultural tourism development, mainly from the perspective of tourism destinations and tourist experience, have rarely explored the cultural tourism development mechanism from the perspective of interest-related community interaction in the film-enabling context. In this study, we conducted high-frequency word analysis and element category analysis of the online text data of the Japanese animation film Your Name from the angle of interest-related community interaction through utilizing online text analysis and Grounded Theory analysis. Based on the interest-related community interaction, we analyzed the elements of interest-related community interaction in cultural tourism triggered by the film, including tourist hotspots, tourism resources, the tourist experience, sightseeing expectations, tourism evaluation and information dissemination, and formulated the orientation pathway of film-enabling cultural tourism. In this study, we aimed to enrich cultural tourism research and provide a reference point and theoretical support for film-enabling cultural tourism in the Internet era by introducing the concept of interest-related community innovation to the scene of film-enabling cultural tourism.